STUDI KOMPARATIF KONSEP KENABIAN DALAM KITAB SUCI AL-QUR’AN, TANAKH, BIBEL DAN WEDA - Najamuddin Makmur; Nurun Nissa Baihaqi; M. Riyan Hidayat; Mahfidatul Khasanah; Aidah Mega Kumalasari (Abrahamic Religions: Jurnal Studi Agama-Agama, 2022)
The concept of prophethood is an issue that is always relevant as long as society requires a comprehensive understanding of it, especially until now there are still emerging parties who claim to be prophets. This paper tries to explain the concept of Prophethood comprehensively with an explanation of the scriptures as a basic understanding of religions. This research uses literature and comparative studies as the method. That is by describing the concept of Prophethood in general and its concepts in the holy books of the Qur'an, Tanakh, Bible and Vedas and explaining the similarities and differences. The concept that has been described will eventually broaden people's understanding and strengthen unity and tolerance. The results of this paper are From the explanation above, it can be concluded that the four holy books (Al-Qur'an, Tanakh, Bible and Vedas have various concepts of prophethood. Comparative theology shows that the similarity of the concept of prophethood in the holy books lies in the superiority of a The prophet who differs from millions of other humans, in his prophetic role or role as well as who sent him. Meanwhile in terms of differences that the four holy books have their own concepts regarding the origin of the Prophet or his descendants, whether to be of Israelite blood or not. the concept of prophethood is also in the names of the Prophet as a person